2015
DOI: 10.1111/apt.13142
|View full text |Cite
|
Sign up to set email alerts
|

Review article: the safety of therapeutic drugs in male inflammatory bowel disease patients wishing to conceive

Abstract: SUMMARY BackgroundMany therapeutic drugs are used by patients with inflammatory bowel disease, often around the time of conception. The pregnancy outcomes of males and females exposed to these therapeutics needs to be examined and this information is necessary to counsel patients appropriately.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
2

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 58 publications
(36 citation statements)
references
References 53 publications
0
34
0
2
Order By: Relevance
“…We know that AZA/6-MP are embryotoxic and teratogenic when given to pregnant female mice and rabbits at high doses,1–3 and we also know that AZA/6-MP cause chromosomal abnormalities in the sperm of male mice 4 5. Although there have been a number of studies on the birth outcomes of children delivered by mothers who took AZA/6-MP during conception and pregnancy,6–15 there is little data on the effect of AZA/6-MP on human sperm and the possible effect on the birth outcomes of children whose fathers took AZA/6-MP at the time of conception 16. Previous reports of AZA/6-MP in men have been limited by the small numbers of patients studied, and statistical significance of an adverse birth outcome was difficult to achieve 15 17–19.…”
Section: Introductionmentioning
confidence: 99%
“…We know that AZA/6-MP are embryotoxic and teratogenic when given to pregnant female mice and rabbits at high doses,1–3 and we also know that AZA/6-MP cause chromosomal abnormalities in the sperm of male mice 4 5. Although there have been a number of studies on the birth outcomes of children delivered by mothers who took AZA/6-MP during conception and pregnancy,6–15 there is little data on the effect of AZA/6-MP on human sperm and the possible effect on the birth outcomes of children whose fathers took AZA/6-MP at the time of conception 16. Previous reports of AZA/6-MP in men have been limited by the small numbers of patients studied, and statistical significance of an adverse birth outcome was difficult to achieve 15 17–19.…”
Section: Introductionmentioning
confidence: 99%
“…inflammatory bowel disease, can cause fertility impairment. However, corresponding drug therapy has been judged as the main factor . Sulfasalazine and mesalazine are known to induce reversible oligozoospermia, normalizing two to three months after discontinuation .…”
Section: Discussionmentioning
confidence: 99%
“…Sulfasalazine and mesalazine are known to induce reversible oligozoospermia, normalizing two to three months after discontinuation . Immunosuppressive thiopurines, azathioprine, and its active metabolite mercaptopurine do not appear to reduce fertility . Concerns have been raised regarding chromosomal changes and the manufacturer recommends contraception for men during and six month after therapy .…”
Section: Discussionmentioning
confidence: 99%
“…Human studies are mixed, but there have been no reports of abnormal births to fathers on MTX, and cessation of MTX in this population is likely not necessary. 107 …”
Section: Immunomodulatorsmentioning
confidence: 99%
“…Several earlier studies in the IBD literature reported negative effects on sperm and semen. 27,107,134 Still, further studies in the rheumatological literature have found that anti-TNF-α agents have no negative effects on male fertility and can be continued in patients trying to conceive. 135–137 …”
Section: Biologicsmentioning
confidence: 99%